Pengembangan Bakpao Ikan Tenggiri sebagai Potensi Intervensi Pencegahan Stunting pada Anak Usia Dini dan Ibu Hamil: Study of the Acceptance Level of Mackerel Fish Buns as an Effort to Prevent Stunting - Mukhtar, Thoha; Isnaeni Azizah, Mecha; Fathina Bidzikri, Anwa; Az Zahra, Salsabila; kristiningsih, ari (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2024)
Stunting is a problem related to brain development, resulting in slow motor and mental growth. The issue of stunting is influenced by low access to food, both in quantity and nutritional quality. Mackerel can be used as an alternative food to prevent stunting because of the content it contains. In this study, mackerel was used as a filling in bakpao. Bakpao is one of the traditional Chinese foods that is often used as a snack. This study aims to determine the level of panelist acceptance of mackerel fish bakpao. The contents of mackerel fish bakpao include 76.5% water, 21.4% protein, 0.56% fat, 0.61% carbohydrates and 0.93% ash content. Based on the hedonic test of the parameters of taste, aroma, texture, and color, mackerel fish bakpao was liked by the panelists. Based on these results, bakpao with mackerel fish filling can be used as a food to prevent stunting. Keywords: stunting, bakpao, mackerel fish